Manufacturing Systems: Theory and Practice - Chryssolouris, George; SpringerLink (Online service) (New York, NY : Springer New York, 2006)
Manufacturing Systems: Theory and Practice, Second Edition, provides an overview of manufacturing systems from the ground up. It is intended for students at the undergraduate or graduate level who are interested in manufacturing, industry practicing engineers who want an overview of the issues and tools used to address problems in manufacturing systems, and managers with a technical background who want to become more familiar with manufacturing issues. The book has six chapters that have been arranged according to the sequence used when creating and operating a manufacturing system. Thus, the subjects emphasised are: the decision framework for manufacturing, the manufacturing processes, the manufacturing equipment and machine tools, the design for manufacturing and the operation of manufacturing systems. The book attempts a compromise between theory and practice in all addressed manufacturing systems issues, covering a long spectrum of issues from traditional manufacturing processes to innovative technologies such as Virtual Reality, Nanotechnology and Rapid Prototyping.
Overview of Manufacturing Processes -- Machine Tools and Manufacturing Equipment -- Process Planning -- The Design of Manufacturing Systems -- The Operation of Manufacturing Systems.
Keywords: Engineering; Mechanical engineering; Control engineering; Robotics; Mechatronics; Manufacturing industries; Machines; Tools; Industrial engineering; Engineering; Manufacturing, Machines, Tools; Operating Procedures, Materials Treatment; Control, Robotics, Mechatronics; Mechanical Engineering; Electronic books